2020
DOI: 10.1016/j.isci.2020.101316
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Attenuates Synaptic Transmission and Affects Brain Rhythms Featuring High Energy Expenditure

Abstract: Summary Lactate shuttled from blood, astrocytes, and/or oligodendrocytes may serve as the major glucose alternative in brain energy metabolism. However, its effectiveness in fueling neuronal information processing underlying complex cortex functions like perception and memory is unclear. We show that sole lactate disturbs electrical gamma and theta-gamma oscillations in hippocampal networks by either attenuation or neural bursts. Bursting is suppressed by elevating the glucose fraction in substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(79 citation statements)
references
References 119 publications
2
76
1
Order By: Relevance
“…Moreover, increased D-glucose utilization may result in excessive local L-lactate availability for J o u r n a l P r e -p r o o f synapses. Recent data reported that lactate attenuates glutamatergic synaptic transmission and perturbs network oscillations in gamma and theta-gamma frequency ranges in hippocampal slices [55], again supporting the view that synaptic and cognitive deficits in our model are caused by metabolic dysfunctions.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 87%
“…Moreover, increased D-glucose utilization may result in excessive local L-lactate availability for J o u r n a l P r e -p r o o f synapses. Recent data reported that lactate attenuates glutamatergic synaptic transmission and perturbs network oscillations in gamma and theta-gamma frequency ranges in hippocampal slices [55], again supporting the view that synaptic and cognitive deficits in our model are caused by metabolic dysfunctions.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 87%
“…Indeed, ex-vivo slice studies directly linked lactate-concentration to the disruption the neuronal excitation-inhibition balance, speci cally by reducing gamma-band rhythm due to transient ATP-shortage in fast-spiking inhibitory interneurons 36 . Interestingly, sharp wave-ripples, lower-energy expenditure oscillations characterizing waking immobility and slow-wave sleep, were not perturbed by lactate injection 37 .…”
Section: Discussionmentioning
confidence: 94%
“…Finally, lactate may have a neuroprotective effect through reducing excitotoxicity. Indeed, it was recently shown on hippocampal slices that lactate in the medium can reduce neurotransmitter content at both excitatory and inhibitory synapses, thus limiting excitotoxicity, which is present during hypoxia-ischemia ( Hollnagel et al, 2020 ). To conclude, we can hypothesize that resveratrol, in addition to its antioxidant, anti-apoptotic and anti-inflammatory properties, may also be neuroprotective by targeting key partners of the ANLS.…”
Section: Discussionmentioning
confidence: 99%